Relationship between dietary protein intake and serum essential free amino acid concentrations in Japanese pregnant women: an observational study - Takuya Shibasaki; Hirohiko Nakamura; Takuya Kamimura; Fuka Tabata; Satomi Kawakami; Mayumi Inubashiri; Masayoshi Hosaka; Kiwamu Noshiro; Takeshi Umazume; Kazuhiro Miyaji (BMC Pregnancy and Childbirth)
Abstract Background Insufficient protein intake decreases serum free amino acid (FAA) concentrations and worse whole-body nutritional status, leading to poor pregnancy outcomes. Protein can be obtained from various dietary sources and differs in amino acid composition. However, it remains unclear whether FAA patterns and nutritional status are influenced by differences in dietary protein sources. Therefore, this study aimed to explore the relationship between serum FAAs, type of protein source intake, and protein nutritional status to improve diet during pregnancy. Methods In this secondary analysis of data from an observational study of pregnant Japanese women (n = 115), we examined the relationship between serum FAA concentrations, the intake of each protein source, and protein nutritional status. Serum FAA concentrations and protein nutritional biomarkers were measured, and the intake of each protein source was estimated using a brief self-administered diet history questionnaire. Results Serum FAA concentrations were significantly positively correlated with animal protein intake. Weight-adjusted total and animal protein intakes in the first tertile (T1) of the reduced albumin (Alb) ratio were significantly lower than those in the second and third tertiles (T2-3). Tryptophan concentrations in the second and third trimesters of pregnancy were significantly positively correlated with the reduced Alb ratio. Threonine in T1 of the reduced Alb ratio was significantly lower than that in T2-3 in the second trimester. Conclusions Individual FAA concentrations during pregnancy are affected differently according to the dietary protein source and intake. The intake of animal proteins is effective in maintaining essential FAAs during pregnancy. Protein deficiency may lead to decreased concentrations of serum tryptophan, threonine, and protein nutritional biomarkers. Identifying a proper strategy for ensuring adequate protein intake may contribute to healthy birth outcomes. Graphical Abstract Inadequate protein intake decreases serum free amino acid concentrations, leading to poor overall nutritional status and poor pregnancy outcomes. Animal protein intake and reduced albumin, a novel indicator of protein nutrition, were significantly associated with serum tryptophan and threonine concentrations. Animal protein intake is effective in maintaining essential free amino acid concentrations during pregnancy and may contribute to healthy birth outcomes. Trp, tryptophan; Thr, threonine; Phe, phenylalanine; Met, methionine; Lys, lysine; BCAAs, branched-chain amino acids; His, histidine.